A new invertebrate NPY-like polypeptide, ZoaNPY, from the Zoanthus sociatus, as a novel ligand of human NPY Y2 receptor rescues vascular insufficiency via PLC/PKC and Src- FAK-dependent signaling pathways - Qian Chen; Nan Xu; Chen Zhao; Yulin He; Sandy Hio Tong Kam; Xue Wu; Pan Huang; Min Yang; Clarence Tsun Ting Wong; Gandhi Radis-Baptista; Benqin Tang; Guangyi Fan; et al. (Elsevier, 2024)
Our recent multi-omics studies have revealed rich sources of novel bioactive proteins and polypeptides from marine organisms including cnidarians. In the present study, we initially conducted a transcriptomic analysis to review the composition profile of polypeptides from Zoanthus sociatus. Then, a newly discovered NPY-like polypeptide-ZoaNPY was selected for further in silico structural, binding and virtually pharmacological studies. To evaluate the pro-angiogenic effects of ZoaNPY, we employed an in vitro HUVECs model and an in vivo zebrafish model. Our results indicate that ZoaNPY, at 1-100 pmol, enhances cell survival, migration and tube formation in the endothelial cells. Besides, treatment with ZoaNPY could restore a chemically-induced vascular insufficiency in zebrafish embryos. Western blot results demonstrated the application of ZoaNPY could increase the phosphorylation of proteins related to angiogenesis signaling including PKC, PLC, FAK, Src, Akt, mTOR, MEK, and ERK1/2. Furthermore, through molecular docking and surface plasmon resonance (SPR) verification, ZoaNPY was shown to directly and physically interact with NPY Y2 receptor. In view of this, all evidence showed that the pro-angiogenic effects of ZoaNPY involve the activation of NPY Y2 receptor, thereby activating the Akt/mTOR, PLC/PKC, ERK/MEK and Src- FAK-dependent signaling pathways. Furthermore, in an excision wound model, the treatment with ZoaNPY was shown to accelerate the wound healing process in mice. Our findings provide new insights into the discovery and development of novel pro-angiogenic drugs derived from NPY-like polypeptides in the future.